Effect of Sound Waves with Different dB Values at 1000 Hz Frequency on Some Aroma Substances in Strawberry Fruits - Ozkurt, Halil (European Scientific Journal, ESJ, 2020)
Plants are exposed to various environmentalstresses during cultivation in plant production. Several defense mechanisms come into action together with many physiological changes in the plant after itfaces stress conditions. Sound waves are among the abiotic stress factors in vegetable production. In this study, which examined the effects of sound waves at 3 different dBs (95 dB, 100 dB, and 105 dB) at1000 Hz frequency value on aroma substances in strawberry fruits, it was assumed that sound stress could increase taste and aroma substances; therefore, it would have positive effects on the quality of the fruit. Strawberry, which is in the berry fruit group, is one of the most common fruit types in the world. Strawberry can be consumed after processing as well as after-ripening during periods when fresh fruit is low in the marketand is rich in vitamins. Nineteen volatile taste and aroma substance analyses were performed in the fruit after a 30-day trial in strawberry plants in pots that were placed in chambers where sound stress was applied at different dBs. As a result of the analyses, it was determined that as the dB increased, so did the taste and aroma of materials, increasing the quality and marketing rate of the fruit.